Selected women's swimsuit style preference based on their age group and body shape - Belludo, Andrea Lauren Z.; Caragay, Kristyn T. (Quezon City College of Home Economics, University of the Philippines Diliman, 2018)
This study aimed to identify women's swimsuit styles preferences based on age group (teens,young adults, adults) and the perceived and actual body shapes (rectangle, triangle, inverted triangle, hourglass, and circle). It looked into the actual body shapes of the respondents and the different body features that they sought to emphasize and de-emphasize. Ninety (90) female respondents from UP Diliman were purposively selected and equally divided into 30 respondents each age group. It was found that regardless of age and body shape, one-piece was the most preferred basic swimsuit style.The most commonly preferred swimsuit details were the following: triangle (neckline style), halter (strap style), cross back (back detail), boyleg (front bottom detail), moderate coverage (back bottom detail), covered 2 (midriff style), and board shorts (cover-up). It was found that based on these selections, the respondents,regardless of age and body shape, desired for maximum coverage for their lower body parts, whereas they most commonly sought enhancement and support for their upper body parts.It was also found that swimsuit style preference was significantly related to body shape and age.This study's findings could potentially provide essential information regarding the purchase decision by women with regard to swimsuit styles. Furthermore, the research results suggest that an in-depth research and additional studies regarding the factors that affect the style selections, such as coverage, support, enhancement of different body parts, and why women perceive tan lines as aesthetically pleasing could be beneficial.
Submitted January 2018.
Thesis (B.S. Clothing Technology)--University of the Philippines Diliman.
Keywords: Bathing suits -- Philippines